2016
DOI: 10.1111/resp.12789
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for lung cancer

Abstract: Treatment of lung cancer remains a challenge, and lung cancer is still the leading cause of cancer-related mortality. Immunotherapy has previously failed in lung cancer but has recently emerged as a very effective new therapy, and there is now growing worldwide enthusiasm in cancer immunotherapy. We summarize why immune checkpoint blockade therapies have generated efficacious and durable responses in clinical trials and why this has reignited interest in this field. Cancer vaccines have also been explored in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
267
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 293 publications
(269 citation statements)
references
References 88 publications
0
267
0
2
Order By: Relevance
“…37 These findings led to US Food and Drug Administration (FDA) approval of ipilimumab as a first-line therapy for advanced melanoma in 2011. 5,6,25 Preclinical murine studies have corroborated this, with aPD-1 observed to augment antitumor responses and delay metastasis in models of melanoma, colorectal and pancreatic cancer. 2,5 Recently, a phase-II trial investigating tremelimumab, an IgG2 antibody targeting CTLA-4, in patients with relapsed malignant mesothelioma found no significant improvement to survival compared to placebo.…”
Section: Actla-4mentioning
confidence: 81%
See 4 more Smart Citations
“…37 These findings led to US Food and Drug Administration (FDA) approval of ipilimumab as a first-line therapy for advanced melanoma in 2011. 5,6,25 Preclinical murine studies have corroborated this, with aPD-1 observed to augment antitumor responses and delay metastasis in models of melanoma, colorectal and pancreatic cancer. 2,5 Recently, a phase-II trial investigating tremelimumab, an IgG2 antibody targeting CTLA-4, in patients with relapsed malignant mesothelioma found no significant improvement to survival compared to placebo.…”
Section: Actla-4mentioning
confidence: 81%
“…5,17 Despite this, research indicates these cells may be functionally tolerant to tumor antigen in lung cancer, characterised by dysregulated cytotoxic function and exhaustion. 5,17 Despite this, research indicates these cells may be functionally tolerant to tumor antigen in lung cancer, characterised by dysregulated cytotoxic function and exhaustion.…”
Section: Regulatorymentioning
confidence: 99%
See 3 more Smart Citations